A further manuscript source for Proclus' Hymns - Thomas, Oliver (Cambridge University Press, 2017)
Bruxellensis 11377-80 ff. 1-4 contains a previously uncatalogued text of Proclus Hymns 3.12-7.52 and Orphic fr. 31 Bernabé, copied by Demetrios Moschos in c.1490 from Mutinensis Est. gr. 164.